Evaluation of the "release and perfuse technique" for aortic arch surgery. Issue 9 (22nd May 2022) - Piperata, Antonio; d'Ostrevy, Nicolas; Busuttil, Olivier; Avesani, Martina; Modine, Thomas; Lorenzoni, Giulia; Azzolina, Danila; Labrousse, Louis; Pernot, Mathieu
Abstract: Objectives: The hypothermic circulatory arrest is a major limitation of the frozen elephant trunk (FET) technique, associated with a high incidence of postoperative mobility and mortality. The aim of this study was to evaluate the surgical outcomes of patients suffering from different aortic arch diseases treated with the release and perfuse technique (RPT). Methods: We retrospectively reviewed the records of patients who had undergone aortic arch repair with the RPT at our Institution between October 2019 and September 2021. Preoperative, intra‐operative, and postoperative data were collected. Results: A total of 18 patients undergoing aortic arch surgery with the use of RPT were analyzed. Twelve of them (67%) were males, and the median age of the entire cohort was 67 (56–73) years. The primary indications for surgery included acute type A aortic dissection (50%), chronic type B aortic dissection (33%), and chronic aneurysms (17%). The median cardiopulmonary bypass‐, aortic cross‐clamp‐ and circulatory arrest times were 163 (147–213) min, 69 (51–120) min, and 10 (8–13) min, respectively. The median intensive care unit and hospital stay were 4 (2–7) and 12 (11–16) days, respectively. One patient (6%) died during the first 30 days after surgery. Conclusions: Considering the anatomical limitations related to the use of this technique, the RPT can be safely performed and could represent a promising strategy to reduce the circulatory arrest time during aortic arch surgery. Nevertheless, further studies are required to demonstrate its efficacy.